Taking the Translational Science Benefits Model from concept to operationalization: opportunities and challenges in defining impact using the Translational Science Benefits Model - Sperling, Jessica; Ghanem, Eman; Quenstedt, Stella; Saxena, Tarun (Frontiers in Public Health, 2025)
The Translational Science Benefits Model (TSBM) was developed to conceptualize and communicate the benefits and impact of translational research. While the TSBM was developed as a conceptual model rather than an operational process, it can be integrated into operational processes to provide evidence and clearly explain the impact of translational research and translational science. This paper discusses the use of the TSBM not only as a conceptual framework but also as a program-integrated operational mechanism. First, it discusses three TSBM-informed programmatic processes for addressing intended and achieved impact: case studies, Pilots program reporting, and an organizational database. Then, it outlines the key factors emerging from these processes that should be considered before employing TSBM as an integrated structure for collecting information on translational research outcomes. In particular, this paper discusses key who questions with a focus on who codes or reports TSBM data, including accounting for the coder or reporter’s understanding of the TSBM, while balancing feasibility with validity. Key how questions including a specific focus on how potential TSBM outcomes are defined and determined. Key when questions address potential limitations or adaptation needs in TSBM-based measurement based on specific areas of focus, particularly workforce development and translational science-specific outcomes. Ultimately, this paper provides key lessons to consider when using the TSBM as a data collection tool and also explores opportunities to expand the utility of the TSBM as a data collection tool to understand, demonstrate, and augment the impact of translational research and science.